Newborn Blood Spot Screening Test Using Multiplexed Real-Time PCR to Simultaneously Screen for Spinal Muscular Atrophy and Severe Combined Immunodeficiency. (6th January 2020) - Taylor, Jennifer L; Lee, Francis K; Yazdanpanah, Golriz Khadem; Staropoli, John F; Liu, Mei; Carulli, John P; Sun, Chao; Dobrowolski, Steven F; Hannon, W Harry; Vogt, Robert F
Abstract: BACKGROUND: Spinal muscular atrophy (SMA) is a motor neuron disorder caused by the absence of a functional survival of motor neuron 1, telomeric ( SMN1 ) gene. Type I SMA, a lethal disease of infancy, accounts for the majority of cases. Newborn blood spot screening (NBS) to detect severe combined immunodeficiency (SCID) has been implemented in public health laboratories in the last 5 years. SCID detection is based on real-time PCR assays to measure T-cell receptor excision circles (TREC), a byproduct of T-cell development. We modified a multiplexed real-time PCR TREC assay to simultaneously determine the presence or absence of the SMN1 gene from a dried blood spot (DBS) punch in a single reaction well. METHOD: An SMN1 assay using a locked nucleic acid probe was initially developed with cell culture and umbilical cord blood (UCB) DNA extracts, and then integrated into the TREC assay. DBS punches were placed in 96-well arrays, washed, and amplified directly using reagents specific for TREC, a reference gene [ribonuclease P/MRP 30kDa subunit ( RPP30 )], and the SMN1 gene. The assay was tested on DBS made from UCB units and from peripheral blood samples of SMA-affected individuals and their family members. RESULTS: DBS made from SMA-affected individuals showed no SMN1- specific amplification, whereas DBS made from all unaffected carriers and UCB showed SMN1 amplification above a well-defined threshold. TREC and RPP30 content in all DBS were within the age-adjusted expected range. CONCLUSIONS: SMA caused by the absence of SMN1 can be detected from the same DBS punch used to screen newborns for SCID.